(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Studying the relation of groundwater and surface water is complex, and concerns not only the hydraulic parameters of a river or channel, but also many other factors; that is, the climatic conditions of the region, the morphology of the river valley, and the soil-geological structure of the region due to land reclamation conditions. For the design and operation of irrigation and drainage facilities, it is often necessary to solve the problems of water exchange on a regional scale accounting for the interaction of surface and groundwater (i.e., the estimation of the amount of groundwater, the distribution of river flow throughout the year, river basin particularities, the construction of irrigation and drainage systems, etc.). Nowadays, the effective use of water resources, and especially the further improvement of hydro-systems of river basins, is one of the important issues in Uzbekistan. Along with the changes in the hydrological regime of rivers, their influence on groundwater is also increasing due to climate change. The change in the level of underground water in irrigated areas and its regime is of particular importance. Therefore, the elaboration of methods for assessing the dependence of the underground water regime on the overall hydrological regime of rivers, as well as new approaches to improving the means of irrigation and land reclamation become an essential priority. This research work was conducted in the framework of solving the above-mentioned issues and to assess the impact of the change of the hydrological regime of the Karasuv River on the irrigated areas of the region around.